2016
DOI: 10.1016/s2213-2600(16)30033-9
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre evaluation of multidisciplinary team meeting agreement on diagnosis in diffuse parenchymal lung disease: a case-cohort study

Abstract: National Institute of Health Research, Imperial College London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
270
2
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 372 publications
(302 citation statements)
references
References 26 publications
9
270
2
21
Order By: Relevance
“…In these patients, the diagnosis of connective tissue disease-related ILD is usually straightforward and might spuriously increase overall diagnostic agreement [15].…”
Section: Case Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these patients, the diagnosis of connective tissue disease-related ILD is usually straightforward and might spuriously increase overall diagnostic agreement [15].…”
Section: Case Collectionmentioning
confidence: 99%
“…The scoring protocol has been described previously [15]. For each case, physicians were required to select up to five differential diagnoses and provide a diagnostic likelihood (censored at 5% and summing to 100% in each case) from a drop-down menu of diffuse lung diseases (supplementary table A3) based upon their diagnostic confidence.…”
Section: Scoring Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many cases, making a confident diagnosis of HP is hampered by marginal test results, nonspecific HRCT features and perhaps most importantly, the lack of internationally agreed diagnostic guidelines for the disease. These difficulties were brought into sharp relief by a recent study of multidisciplinary practice that reported miserable diagnostic agreement (weighted κ-coefficient (κw)=0.29) between expert multidisciplinary groups assigning a diagnosis of HP to a set of standardised cases drawn from a tertiary referral centre for diffuse lung diseases [2]. In contrast, interobserver agreement for idiopathic pulmonary fibrosis (IPF) was good (κw=0.71), reflecting the positive impact evidence-based guidelines have on diagnostic performance.…”
mentioning
confidence: 99%
“…For these reasons, radiological diagnosis should be validated against outcome. This approach has been used in an international study of multidisciplinary IPF diagnosis and to verify the diagnostic accuracy of a novel Deep Learning algorithm for classifying fibrotic lung disease on HRCT [2,16]. It is also an approach endorsed by the Standards for Reporting of Diagnostic Accuracy initiative [17,18].…”
mentioning
confidence: 99%